2020
DOI: 10.1093/cid/ciaa1536
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based Guideline for Therapeutic Drug Monitoring of Vancomycin: 2020 Update by the Division of Therapeutic Drug Monitoring, Chinese Pharmacological Society

Abstract: Background Clinical practice guidelines or recommendations often require timely and regular updating as new evidence emerges, because this can alter the risk-benefit trade-off. The scientific process of developing and updating guidelines accompanied by adequate implementation can improve outcomes. To promote better management of patients receiving vancomycin therapy, we updated the guideline for the therapeutic drug monitoring (TDM) of vancomycin published in 2015. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
117
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(127 citation statements)
references
References 33 publications
4
117
1
5
Order By: Relevance
“…On the other hand, extensive antibiotic treatments in COVID-19 patients [ 47 ] may perturb gut homeostasis, allowing bacterial pathogens to cause pneumonia or other invasive infections [ 48 ]. Consistent with a significantly altered gut microbiota of COVID-19 patients compared to healthy controls [ 49 ], our 16S rRNA gene sequencing data show that the lung bacterial community of patients with COVID-19 was different from that of patients without COVID-19 ( P = 0.004). Interestingly, Olsenella and Streptococcus anginosus , which normally inhabit the oropharynx forming biofilm to enhance bacterial adherence and thriving [ 50 ], were among the taxa significantly enriched in the COVID-19 lung microbiota together with SA.…”
Section: Discussionsupporting
confidence: 82%
“…On the other hand, extensive antibiotic treatments in COVID-19 patients [ 47 ] may perturb gut homeostasis, allowing bacterial pathogens to cause pneumonia or other invasive infections [ 48 ]. Consistent with a significantly altered gut microbiota of COVID-19 patients compared to healthy controls [ 49 ], our 16S rRNA gene sequencing data show that the lung bacterial community of patients with COVID-19 was different from that of patients without COVID-19 ( P = 0.004). Interestingly, Olsenella and Streptococcus anginosus , which normally inhabit the oropharynx forming biofilm to enhance bacterial adherence and thriving [ 50 ], were among the taxa significantly enriched in the COVID-19 lung microbiota together with SA.…”
Section: Discussionsupporting
confidence: 82%
“…Despite COVID-19 being a novel disease, in this review, there was very good representation of patients from different care-settings and age groups, with several different comorbidities. The reports included both females and males, with the exception of some case reports and a few studies on gender-specific populations such as patients in a maternity ward [ 39 ]. Reports from China, the first country to publish descriptions on COVID-19-specific symptoms, focused on core symptoms such as fever, cough, shortness of breath and diarrhoea and a large proportion of patients across all ages needed hospital admission and intensive care.…”
Section: Discussionmentioning
confidence: 99%
“…A study on 30 patients with COVID-19 also showed that the gut microbiome was associated with a dysbiosis compared to healthy controls. COVID-19 patients showed a significantly reduced bacterial diversity due to an overgrowth of opportunistic pathogens ( Streptococcus , Rothia , Veillonella and Actinomyces ) and a decrease of beneficial symbionts [ 246 ]. Another group worked on the transcriptional activity of SARS-CoV-2 in the feces of 15 patients with COVID-19 and showed that the gut microbiome was correlated to the viral transcriptional activity [ 247 ].…”
Section: Covid 19: Relevance Of Host Genetic Factorsmentioning
confidence: 99%